Continuous-feed carbonation of waste incinerator bottom ash in a rotating drum reactor. (November 2019) - Brück, Felix; Ufer, Kristian; Mansfeldt, Tim; Weigand, Harald
Highlights: Bottom ash was carbonated under continuous feed conditions in a rotating drum reactor. Residence times of 80 min were sufficient for trace metal immobilisation. The leachate concentrations of critical trace metals decreased by at least one order of magnitude. Increasing the temperature and moisture of the reactant gas did not impede carbonation. Abstract: Carbonation is a key process in the aging of waste incinerator bottom ash (BA). The reaction with CO2 decreases the BA alkalinity and lowers the leachability of amphoteric trace metals. Passive ageing over several months is usually performed in intermittently mixed BA heaps. Here we aimed at accelerating the process in a rotating drum reactor continuously fed with the BA and the reactant gas (10 vol-% CO2, volumetric flow rate 60 L/min). In one test, the gas was heated and humidified. Since carbonation depends on the specific CO2 -supply, experiments were conducted at varied BA residence time (60, 80, and 100 min). Residence time was calculated by mass balancing and confirmed by the breakthrough time of two tracers. Leachates and solid phase properties of the treated BA served to evaluate the carbonation performance. The residence time of BA could be adequately controlled by the reactor loading and feed rate. A residence time of 80 min was sufficient to reduce the BA leachability such as to comply with the German regulatory standards for non-hazardous waste, whereas the untreated BA was hazardous waste. Decreased alkalinity was indicated by lower leachate pH and Ca(OH)2 contents of the BA as compared to the input. Leachate concentrations of amphoteric trace metals (Pb, Zn, Cu) decreased by at least one order of magnitude while oxyanions became slightly more mobile upon carbonation. In view of relatively short residence times and stable process performance, the rotating drum reactor seems promising for a full-scale implementation of BA carbonation.